The Prevalence of Mental Disorders (Depression and Anxiety) and its Related Factors Among the Elderlies in Bastam, 2018 - Afzali 1*, Abolfazl; Ebrahimi 2, Hossein; Emamian 3, Mohammad Hasan (Shahroud Journal of Medical Sciences, 2019)
Background: Depression and anxiety are common problems in the elderly, which also causes disability and physical illness. The aim of this study is to investigate The Prevalence of Mental Disorders (Depression and Anxiety) and factors affecting them among the elderlies of Bastam city. Method: This study is a descriptive cross-sectional study. By referring to Bastam Health Center, 262 adults aged 60 and over were selected by simple random sampling method. Depression and anxiety in the elderly were measured using the Geriatric Depression Scale and Beck Anxiety Inventory, respectively. To analyze the data, descriptive statistics and inferential statistics including independent t-test, Pearson correlation test and Chi-square test were used. Result: In the present study, 25.6%, 11.1% and 8% of the elderly had mild, moderate and severe depression, respectively. There was no significant difference between depression scores in terms of gender, marital status and employment status (P.V> 0.05); But there was a significant difference between the mean depression scores in terms of underlying disease (P.V <0.001). There was a significant difference between the mean score of anxiety in terms of gender, marital status, occupational status and underlying disease (P.V ≤0.05). There was a direct and significant relationship between age and mean score of depression and anxiety. Also, there was a significant negative correlation between the level of education of the elderly and depression and anxiety scores (P.V ≤ 0.05). Conclusion: Depression and anxiety are prevalent among elderly people in Bastam. Therefore, it is important to address mental health problems, especially depression and anxiety in the elderly, and to identify risk factors among the elderly.